Особенности микроморфологии поверхности граней кристаллов CAC2O4 · H2O; Кристаллография; Т. 62, № 4 - Полиенко А. К. Александр Константинович; Осадчий В. К. Владислав Константинович; Парначёв В. П. Валерий Петрович; Севостьянова О. А. Ольга Александровна (2017, 2017)
Заглавие с экрана